Microfracture for medium size to large knee chondral defects has limited long‐term efficacy: A systematic review - Varun Gopinatth; Garrett R. Jackson; Daniel C. Touhey; Jorge Chahla; Matthew V. Smith; Matthew J. Matava; Robert H. Brophy; Derrick M. Knapik (Journal of Experimental Orthopaedics)
Abstract Purpose To evaluate clinical and radiographic outcomes, return to sport, failure rate, operations and complications in patients undergoing microfracture of the knee, including the femoral condyle, tibial plateau, patella and trochlea, at a mean 10‐year or greater follow‐up. Methods A literature search was performed by querying SCOPUS, PubMed, Medline and the Cochrane Central Register for Controlled Trials from database inception through May 2023 according to the 2020 Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Inclusion criteria were level I‐IV human studies reporting on outcomes, reoperations and complications following microfracture of the knee at a mean 10‐year or greater follow‐up. Biomechanical and epidemiological studies, including patients undergoing concomitant realignment procedures, and studies with patients under 18 years old were excluded. Data regarding failure, as defined by each study, as well as reoperations were gathered. Study quality was assessed via the Methodological Index for Nonrandomized Studies criteria. Results Nine studies from 2003 to 2018, consisting of 727 patients (mean age 38.9 ± 8.1 years; range 25.8–47.6) undergoing microfracture for chondral defects in the knee were identified. Mean follow‐up ranged from 10 to 17 years. Males composed 56.5% of patients, with a mean defect size ranging from 2.3 to 4.01 cm2. Based on radiographs at follow‐up, osteoarthritis progression occurred in 40%–48% of patients. Magnetic Resonance Observation of Cartilage Repair Tissue scores were low. Patient‐reported outcome measures showed significant improvement in postoperative scores at final follow‐up. Return‐to‐sport rate ranged from 17.2% to 20%. Longitudinal analysis revealed declining clinical outcomes and return‐to‐sport rates from short‐ and mid‐ to long‐term follow‐up. There was high variability in failure definition and reoperations, with 2.9%–41% of patients requiring total knee arthroplasty. Conclusions At a mean 10‐year or greater follow‐up, microfracture for chondral defects of the knee 2–4 cm2 in size demonstrated a high rate of osteoarthritis progression with poor healing of the chondral defect and low overall return‐to‐sport rates. Failure and reoperation rates ranged from 2.9% to 41%, with declining outcomes from short‐ and mid‐ to long‐term follow‐up. The advantages of microfracture relating to availability, complexity, and cost should be weighed against concerns about long‐term success, particularly with medium‐size and larger lesions. Level of Evidence Level IV systematic review.